Very high incidence of germ cell tumorigenesis (seminomagenesis) in human papillomavirus type 16 transgenic mice. - Kondoh, G (1991)
Human papillomavirus type 16 (HPV16) is frequently found in carcinomas and precancerous lesions of the uterine cervix and is thought to be closely associated with carcinogenesis in these regions. However, the transforming activity of the E6 and E7 genes in vivo has not been characterized. To investigate this function, we produced transgenic mice carrying HPV16 E6 and E7 open reading frames. We obtained five transgenic founders and established three transgenic lineages. We observed testicular tumors of germ cell origin in mice of all three lineages. Morphological studies showed that these tumors were a type of seminoma. Both testes of all tumor-bearing mice were affected with this type of tumor. Strikingly, in one lineage, all of the male mice developed this tumor. On Northern (RNA) analysis, a high level of expression of HPV mRNA was detected in these tumors. These results suggest that transforming genes of HPV16 have transforming activity in vivo and preferential effects on germ cells in the testis.